GAMBARAN POLA ASUH MAKAN DENGAN STATUS GIZI ANAK USIA 1 â 3 TAHUN DI GAMPONG MEUNASAH BARO KECAMATAN MUARA BATU KABUPATEN ACEH UTARA - Maryam, Siti (Universitas Almuslim, 2013)
Children aged 1-3 years is the period which their need food and nutrition in sufficient and adequate quantities. Lack of nutrition during this period can cause growth disorders. This study aimed to determine the relationship between meal parenting style and nutritional status of children aged 1-3 years in the Gampong Meunasah Baro, Muara Batu, Aceh Utara. This research used descriptive analytic study with cross-sectional design. Data obtained by direct interviews using questionnaires to the mothers with children aged 1-3 years. The results showed the majority of children aged 1-3 years had a normal nutritional status, as much as 92.11 %, most of meal parenting included in good category, as much as 78.95. To mothers who are already applying good parenting, suggested to keep doing it. To mothers who have children who nourished skinny, needs to be given counseling by health workers about good meal parenting in order to improve the nutritional status of children.Â Keywords: parenting style, nutritional status, children aged 1-3 years